PELAKSANAAN PENGAWASAN MINUMAN BERALKOHOL DI KOTA BATAM - Yqhsyah, Raja; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Social problems among the people is always changing and it will continue to follow the dynamics of society itself. Not for the people of Batam City which is the entry point to the neighboring countries of Indonesia, also continues to develop, both positive and negative. As for the negative developments of which consume alcoholic beverages. While the problem of alcohol itself, it can not be denied, it is very disturbing social life. Alcoholic beverages are believed to not only harm the wearer, but also brings a very bad impact on the environment of the wearer. While at this time the spread of alcoholic beverages in the city of Batam, is no longer controlled, for example in its distribution is no longer regard the age limit users or consuming alcoholic beverages that may be negative consequences for children who later adolescence as the future generation. This study was conducted to determine the Alcoholic Beverage Control of Urban Pursuant to Rule Batam conducted by the Department of Industry and Trade of the City of Batam.Research conducted using qualitative methods. This study uses the theory of standard-setting Manullang with supervision. Determination of measurement tools, conduct assessments, conduct remedial action. In this study the technique performed is observation, interview and documentation using qualitative descriptive analysis techniques.In this study was found first, pengawsan by the Department of Trade and Industry is already quite optimal. Secondly, there are still many of his illegal circulation of alcoholic beverages which are not in accordance with local regulations. Third, the lack of public education and sellers of alcoholic beverages. Fourth, still less his understanding and public awareness of the circulation of alcoholic beverages.Keywords: Control, Circulation, Alcoholic Beverages